SURVIVIN EXPRESSION IN ORAL SQUAMOUS CELL CARCINOMA - Antunović, Marija (Sanamed, 2023)
Introduction: Survivin functions as an apoptosis inhibitor and a regulator of cell division. This study aimed to determine the correlation between survivin expression and clinicopathologic parameters of oral squamous cell carcinoma (OSCC) and determine its potential role in the progression/prognosis of this type of tumor. Materials and methods: Immunohistochemical analysis of survivin expression was performed on 45 surgically obtained paraffin-embedded tissue samples of OSCCs. Data on patients’ gender, age, tumor grade, site and stage, disease recurrence, metastasis occurrence, and disease-free interval (DFI) were correlated to survivin expression. Results: Survivin immunoreactivity was observed in 77.8% of samples. No significant correlation between survivin expression and age (p = 0.087), gender (p = 0.334), tumor site (p = 0.175), presence of lymph node metastases (p = 0.201), or disease recurrence (p = 0.451) was found. Survivin expression was observed in well and moderately differentiated tumors and in all clinical stages (p = 0.139). Patients with low survivin expression had better survival rates than the group with medium and high survivin expression, i.e., there was a tendency of a shorter DFI in patients with higher expression of survivin (p = 0.065). Conclusion: There is a tendency for a shorter disease-free period in patients with higher survivin expression. These data suggest that survivin expression in OSCC may act as an additional prognostic parameter that indicates an increased proliferative tumor potential. To further validate survivin as a prognostic marker in OSCC, a study with a larger sample size along with clinical follow-up data is needed.